Associations between sheep farmer attitudes, beliefs, emotions and personality, and their barriers to uptake of best practice: the example of footrot - O’Kane, Holly; Ferguson, Eamonn; Kaler, Jasmeet; Green, Laura (Elsevier, 2017)
There is interest in understanding how farmers’ behaviour influences their management of livestock. We extend the theory of planned behaviour with farmers attitudes, beliefs, emotions and personality to investigate how these are associated with management of livestock disease using the example of footrot (FR) in sheep.